Association of childhood socioeconomic status with edentulism among Chinese in mid-late adulthood - Xiaoning Zhang; Shuang Chen (BMC, 2019)
Abstract Background The aim of this study was to examine the association between childhood socioeconomic status (SES) and edentulism. Methods The edentulous status of Chinese in mid-late adulthood was determined using self-reported lost all of teeth from the Health and Retirement Longitudinal Study (CHARLS). Childhood SES was determined based on the following parameters: the education, occupation and working status of the parents; financial situation of the family; relationship with the parents; care, love and affection from the mother; quarrels and fights between parents; primary residence; neighbors' willingness to help and with close-knit relationships. Adulthood SES was assessed by educational achievements. This study used principal component analysis (PCA) to select variables and binary logistic regression models to determine the association between childhood SES and edentulism. Results Data were available from a total of 17,713 respondents, 984 of whom were edentulous (2.9%). The prevalence of edentulism in mid- to late-age Chinese individuals was higher in those with poor childhood SES. In final regression model, edentulism was significantly associated with willingness of neighbors to help with close-knit relationships (OR = 0.89, 95% CI = 0.79-0.99), parents with high school education or above (OR = 1.18, 95% CI = 1.01-1.39) and drinking and smoking habits of the father (OR = 1.10, 95% CI = 0.97-1.24). Conclusion Childhood SES was significantly associated with the prevalence of edentulism in mid- to late-age Chinese individuals. In particular, parents with high school education or above, unwillingness of neighbor to help with close-knit relationships, drinking and smoking habits of the father independent of adulthood SES were significantly associated with edentulism. Accordingly, the development of optimal recommendations and more effective intervention strategies requires considering the experiences in early life associated with poor SES contributes to poor oral health.